Women’s Autonomy and Decision-making Power through Sustainable Food Gardens: A Gender Analysis of an Urban Community in Indonesia - Adisa Resti Gestasani; Dyah Woro Untari; Mesalia Kriska; Ratih Ineke Wati (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
The Sustainable Food Garden Program (P2L) is a government initiative aimed at strengthening household food systems through community-based gardening involving both women and men. This study examines how participation in P2L affects women’s autonomy and decision-making within households, particularly in the context of gender relations. Using qualitative methods, data were collected through interviews and observations with members of Women Farmers Groups (KWT) Srikandi Mrican, Depok, Sleman, Yogyakarta, and male participants. The Harvard Gender Analysis Framework was applied to assess roles, access to resources, control, and participation factors. Results show that women’s domestic roles allow flexible involvement, while men handle more physically demanding tasks. Overall, P2L fosters a supportive social environment that enhances women’s empowerment, independence, and household influence.